Nano Online 2016
DOI: 10.1515/nano.11671_2015.269
|View full text |Cite
|
Sign up to set email alerts
|

Merging Worlds of Nanomaterials and Biological Environment: Factors Governing Protein Corona Formation on Nanoparticles and Its Biological Consequences

Abstract: (http://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited.Protein corona has became a prevalent subject in the field of nanomedicine owing to its diverse role in determining the efficiency, efficacy, and the ultimate biological fate of the nanomaterials used as a tool to treat and diagnose various diseases. For instance, protein corona formation on the surface of nanoparticles can modify its physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…These proteins are involved in the same cellular processes, namely, complement activation, pathogen recognition and blood coagulation. Despite this similarity in function, they have a different physiological impact on NPs depending on their material [2,45]. Among these, immunoglobulin G, serum albumin, fibrinogen, clusterin and apolipoproteins are generally present in the PC of most analyzed NPs after exposure to plasma [2,46].…”
Section: Composition Of the Pcmentioning
confidence: 99%
“…These proteins are involved in the same cellular processes, namely, complement activation, pathogen recognition and blood coagulation. Despite this similarity in function, they have a different physiological impact on NPs depending on their material [2,45]. Among these, immunoglobulin G, serum albumin, fibrinogen, clusterin and apolipoproteins are generally present in the PC of most analyzed NPs after exposure to plasma [2,46].…”
Section: Composition Of the Pcmentioning
confidence: 99%
“…13) In addition, we previously demonstrated that coagulation factor XII bound more extensively to the surface of nSP70 than to nSP70-N by using Western blot analysis. 8) Therefore, because differences in the surface characteristics of nanomaterials influence the protein profile of the corona, 14) differences in the amount or species of the proteins bound by unmodified compared with surface-modified nSP70s may influence ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction of NPs with biomolecules and composition of the resulting protein corona is affected by many factors (Foroozandeh and Aziz 2015). The physicochemical properties of NPs and the biological environment are vital parameters governing protein corona formation.…”
Section: Properties Of Nps Affecting Protein Corona Formationmentioning
confidence: 99%
“…Negatively charged NPs have been shown for enhancement in plasma protein absorption with an increase in the surface charge density of NPs (Gessner et al 2002). In addition, proteins with isoelectric points (PI) of less than 5.5 adsorbed on positively charged NPs whereas proteins with isoelectric points of higher than 5.5 bound to negatively charged NPs (Foroozandeh and Aziz 2015). More proteins can adsorb onto the surface of hydrophobic NPs than their hydrophilic counterparts and lose their native structure (Roach et al 2005).…”
Section: Properties Of Nps Affecting Protein Corona Formationmentioning
confidence: 99%